Survey of DNA Microsatellites in Differen Varieties of Tomato (Lycopersicon esculentum Mill.) - Miskoska-Milevska, E. (University Ss. Cyril and Methodius - Skopje, Faculty of Agricultural Sciences and Food, Skopje, 2010)
DNA microsatellites are important molecular tools in determination of genetic variability among organisms. The aim of this study was survey of applicability of 12 DNA microsatellites loci in molecular characterization of 6 tomato varieties of Lycopersicon esculentum Mill.: var. grandifolium from subsp. cultum; var. cerasiforme (red and yellow), var. pruniforme and var. pyriforme from subsp. subspontaneum; and var. racemigerum from subsp. spontaneum. The standardization of PCR condition for amplification of 9 polymorphic regions was performed using appropriate primer pairs for the following loci: LECH13, LE21085, LEMDDNa, LEEF1Aa, LELEUZIP, LE20592, TMS9, LE2A11 and LECHSOD. The homozygosity of DNA isolations for locus LE20592 and locus LE2A11 was confirmed by using of DNA sequencing method. The fragment analyses was realized using Applied Biosystems DNA analyzer (ABI 3130) and GeneMapper® Software program. The data were analyzed using the specific programs POWER MARKER SOFTWARE and MEGA3. In the investigated tomato varieties, the highest number of alleles (6) was detected at locus LEEF1Aa and locus LE20592, and only one allele was detected at locus LECHSOD using fragment analyses. For all microsatellites loci in the investigated tomato varieties, the average number of detected alleles was (3,6250). Locus LECHSOD was excluded from the further statistical analyses because of its monomorphicity. In the investigated tomato varieties, three specific alleles were detected at locus LE2A11, two specific alleles were detected at locus LE20592 and per one specific allele were detected at locus LECH13, locus LEMDDNa, locus LEEF1Aa and locus LELEUZIP. For all investigated varieties, the lowest average PIC value was determinated for locus LEMDDNa (0,0601), and the highest average PIC value was determinated for locus LEEF1Aa (0,7552). Average PIC value for all 8 DNA microsatellites loci was (0,3571) and according to classification of Botstein they belong to the group of modest informative markers. In general, all DNA microsatellites showed very high genetic differentiation in the investigated varieties. In the investigated varieties, locus LEEF1Aa, locus LE20592, locus TMS9 and locus LE2A11 showed very big differentiation, locus LEMDDNa showed modest differentiation, and locus LECH13, locus LE21085 and locus LELEUZIP showed very small differentiation. Based on microsatellites loci research, analysis of molecular variance (AMOVA) showed that 25,3 % of the total variance in investigated varieties was between varieties and 74,7 % of the total variance in investigated varieties was within the varieties. The results of genetic distance according to Slatkin, in relation to investigated varieties showed that the lowest genetic distance (16,7415) was noticed between Lycopersicon esculentum subsp. subspontaneum var. cerasiforme (yellow) and Lycopersicon esculentum subsp. subspontaneum var. cerasiforme (red), and the highest genetic distance (34,9859) was noticed between Lycopersicon esculentum subsp. subspontaneum var. pyriforme and Lycopersicon esculentum subsp. cultum var. grandifolium. The results of determination of genetic distance, according to Slatkin, in relation to investigated subspecies showed that the lowest genetic distance (22,1446) was noticed between Lycopersicon esculentum subsp. subspontaneum and Lycopersicon esculentum subsp. spontaneum, and the highest genetic distance (19,7147) was noticed between Lycopersicon esculentum subsp. subspontaneum and Lycopersicon esculentum subsp. cultum. Based on the statistical data, precise dendrograms were created using MEGA3 Software program.
Keywords: Lycopersicon esculentum Mill. DNA microsatellites, genetic distance